Isolated lip involvement in psoriasis: an uncommon aspect of a common dermatologic condition - Bouslama Ghada; Hasni Wafa; Massoud Nour Saida Ben; Youssef Souha Ben; Boughzela Abdellatif (EDP Sciences, 2018)
Introduction: Psoriasis is a chronic inflammatory skin disease that typically affects the extremities, trunk, scalp, and nails. Psoriatic cheilitis as an exclusive presentation is very rare and to our knowledge, only 6 cases have been reported to date. The absence of cutaneous lesions causes diagnostic difficulties that can result in misdiagnosis and inadequate treatment. Observation: We reported the case of a 21-year-old woman with a seven years history of scaly plaques of the vermillion of the lips as the only disease manifestation. Her cheilitis was associated with significant psychiatric morbidity. Oral biopsy showed a psoriasiform pattern. Local applications of betamethasone was proposed. Discussion: Although lip psoriasis is extremely rare, it can be the sole presentation of psoriasis even in the absence of accompanying skin lesions, other oral manifestations or a family history of psoriasis. Conclusion: Lip psoriasis should be considered in the differential diagnosis of chronic or recurrent treatment-resistant labial lesions.